Biogeochemical responses of a highly polluted tropical coastal lagoon after the passage of a strong hurricane (Hurricane Irma). Issue 2 (9th December 2021) - González-De Zayas, Roberto; Merino-Ibarra, Martín; Lestayo González, Julio A.; Chaviano-Fernández, Yida; Alatorre Mendieta, Miguel A.; Pupo, Felipe Matos; Castillo-Sandoval, Fermín S.
Abstract: Laguna Larga (Cayo Coco, Cuba) is a eutrophic coastal lagoon due to tourism development. As part of long-term monitoring of Laguna Larga, we were able to follow the lagoon's water quality from 2015 to 2018 and could assess the impacts of Hurricane Irma (September 8–9, 2017) by intensifying our sampling frequency. Physicochemical parameters (salinity, pH, dissolved oxygen, dissolved inorganic nitrogen, dissolved reactive silicate and total nitrogen) exhibited significant variations associated with Hurricane Irma. Salinity decreased due to the extraordinary rainfall of the hurricane (339.8 mm/24 h, a new record for Cayo Coco). The water level in the lagoon rose 0.85 m. Strong hurricane winds and intense runoff drove organic matter and sediment resuspension. Anoxia and an increase of nutrients occurred throughout the lagoon. The main biogeochemical impact was that it boosted these eutrophic conditions of the lagoon, to levels that lasted for several months. A significant correlation among nutrients, salinity and dissolved oxygen was found. After 6 months, water quality in the lagoon had recovered to conditions similar to those before the hurricane. The case of Laguna Larga shows that those coastal systems under anthropic pressure can take longer to recover after extreme climatic events, and highlights the need for long-term monitoring of tropical coastal ecosystems. HIGHLIGHTS: Long-term monitoring of eutrophic Laguna Larga continued even during the pass of Category 5 Hurricane Irma. The hurricane caused unprecedented impacts: extraordinary rain, water-level rise and a sharp salinity fall. Extended anoxia and extraordinary nutrient peaks boosted eutrophication. It took 6 months for the water quality of the lagoon to return to previous conditions. Anthropized lagoons may take longer to recover. Graphical Abstract